2008
DOI: 10.1068/p5821
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Contrast Makes Speeds in a Video-Based Driving Simulator Harder to Discriminate as Well as Making Them Appear Slower

Abstract: We investigated the effect of reducing image contrast on speed perception using a video-based driving simulator in which participants viewed pairs of scenes and were asked to judge whether the second scene was faster or slower than the first scene. We predicted two outcomes: (i) that vehicle speeds would become harder to discriminate, and (ii) that vehicle speeds would appear slower. There is previous evidence confirming the latter prediction in a less realistic computer-based driving simulation, but none demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
6
37
1
Order By: Relevance
“…Previous studies suggested that the speed of visual motion in depth is underestimated when the global level of contrast is reduced (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). These studies were directly inspired by classical vision research experiments that assessed the effect of contrast on the perceived speed of two-dimensional objects on a monitor (Thompson, 1982; Stone and Thompson, 1992; Blakemore and Snowden, 1999; Anstis, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that the speed of visual motion in depth is underestimated when the global level of contrast is reduced (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). These studies were directly inspired by classical vision research experiments that assessed the effect of contrast on the perceived speed of two-dimensional objects on a monitor (Thompson, 1982; Stone and Thompson, 1992; Blakemore and Snowden, 1999; Anstis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that the perceived speed of two-dimensional moving objects—for example, plaid patterns on a computer screen—is underestimated when visual contrast is reduced. More recent studies based on driving scenarios have suggested that the underestimation of visual speed at low contrast applies also to perceived self-motion in three-dimensional environments (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). This finding was proposed—and is still considered—as a possible explanation for excessive driving speed in fog.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impairs distance perception, which can prompt rear end collisions (Broughton et al, 2007;Buchner et al, 2006;Cavallo et al, 2001). It also causes drivers to underestimate how rapidly other vehicles are traveling (Horswill and Plooy, 2008;Snowden et al, 1998). Furthermore, because objects have to be closer to become fully visible, fog reduces the amount of time drivers have to react to stimuli in the environment.…”
Section: Introductionmentioning
confidence: 94%
“…An analysis of speeding records conducted by Cherry and Andrade (2001) indicates that brightly colored vehicles regularly receive tickets for comparatively lower speeds, meaning that bright color may lead to overestimations of speed. Horswill and Plooy (2008) investigated the effect of reducing image contrast on speed estimation in a simulated experiment and found vehicle speeds were perceived to be slower in reduced contrast condition. A common weather condition that may reduce the contrast is a rainy condition, as the heavy sky is gloomy and the raindrops block the line of sight.…”
Section: Speed Estimationmentioning
confidence: 99%